Intelligent decision support systems in marketing managelement - Öngüç, Hakan (My University, 2002)
Bu tez pazarlama yonetimi alaninda akilli karar destek sistemi kurmayi savunur. Literatur'de ES ve DSS hakkinda bir cok makale ve kitap mevcuttur. Bu tezin ana savundugu nokta sudur: Karar destek sureci, karar vericiyi acik bir sekilde destekleyen akilli karar destek sistemi kurarak iyilestirilebilir. DSS ve ES kuramlarina ayri ayri baktigimiz zaman, ikisinin de avantaj ve dezavantajlarinin oldugunu goruruz. Bu da iki sistemin entegrasyonu ile daha iyi bir karar destek sistemi kurulabilir mi sorusunu ortaya cikarmaktadir. Literature baktigimiz zaman bu iki sistemin entegrasyonu konusunda acikca fazla durulmadigi gorulmektedir. Bu durum beni bu konu hakkinda arastirma yapmaya tesvik etmistir. Yukaridaki problemlere dayanarak, bu tezin amaclari soyle siralanabilir; (1) mevcut literaturdeki makale ve yayinlarin incelenmesi ve ES/ DSS uygulamalarinin ortaya cikarilmasi; (2) bu iki sistemin en iyi sekilde entgrasyonu icin yeni bir metodun onerilmesi; (3) ES ve DSS entegraasyonunun, karar verme surecini iyilestirdigini gostermek icin kavramsal bir modelin ve prototipin gelistirilmesi; (4) Karar destek surecini basindan sonuna kadar destekleyecek bir metodun, onerilen modele entegre edilmesi; (5) gelisitirilen entegre modelin pazarlama yonetimi alanina uyarlanmasi; (6) ve son olarak, onerilen modelin mevcut limitlerinin belirlenmesi ve ileriye donuk arastirma alanarinin tavsiye edilmesi. Bu noktada, bir konuyu vurgulamak gerekmektedir. Bu tezin amaci tamamen entegre bir modelin kurulmasi, tasarlanmasi, gelistirilmesi degildir. Bu konu, bu tezin amacinin disindadir. Bu tezin amaci, DSS ve ES modellerinin entegre model prototipi olarak tasarlanmasi ve tasarlanan entegre modeling yukarida belirttigimiz problemleri nasil cozebilecegini ve karar verme surecini nasil iyilestirilebilecegini gostermektir. This thesis proposes to develop an intelligent Decision support system in Marketing Management Area. There are a lot of researches conducted in the literature in the fields of ES and DSS. The basic premise of this thesis is that decision-making process could be greatly enhanced by explicitly assisting decision makers by proposing integrated intelligent models. When we look at the pros and cons of these two methodologies, it is obvious that DSS and ES can be integrated and this can improve the quality of decision support process for the business. In the Literature, the integration of these two important fields are not discussed and analyzed very well. The research conducted in this thesis was motivated by above issues that were not properly covered in the literature. Based on the above issues, the objectives of this thesis are; (1) to review the existing literature to identify the gaps in current practices of ES and DSS methodologies, (2) to define the best-fitting integration methods of these two methodologies to improve the decision making process, (3) to develop a conceptual framework and prototype to prove how this integrated model can improve the decision making of the business; (4) to define a method of embedding process-wised decision support requirements within the intelligent decision support systems framework and the prototype; (5) to apply this integrated framework to one of the important decision making area in business planning: marketing planning which mainly deals with semi-structured and/ or unstructured problems; (6) and finally to define the limitations of the integrated model and propose future work and improvement areas. I would like to stress out again that my objective in this thesis is not to develop and implement a complete intelligent marketing management system. This is beyond the objective of the thesis. My objective is to discuss the benefits of IDSS solution and demonstrate its benefits by using a prototype model. The prototype is designed to highlight the integration touch points and its potential business implications in marketing management area.
Keywords: Genel yönetim; Pazarlama Yönetimi